Dimension of green skills: perspectives from the industry experts - Mohd Zubir, Muhammad Zulfadly; Chee, Sern Lai; Zaime, Adib Farhan; Ming, Foong Lee; Ibrahim, Badaruddin; Ismail, Affero (Penerbit UTHM, 2021)
The environmental issue was a debating topic over the past decades, but the knowledge, skill, and attitude among the people are still never changed. Several studies found that a huge contributor to waste is the industrial sector. Due to that, the green industry policies were created for environmental justice in order to minimise the greenhouse gases, and the creation of the green industries was started. The green industries were opening jobs opportunity for green jobs, and fulfilling the jobs that required someone competent with green skills. To be competent, they needed in mastering the three dimensions of green skills: knowledge, skill, and attitude. However, the skill shortage among the workers arose. Therefore, this paper aimed to explore green skills elements from the industrial perspective in skill dimension. In this study a Delphi technique were applied which started with interview session among experts. The semi-structured interview was conducted, and the protocol interview was validated through peer review and member checking. Six experts were selected from the green industries and the selection according to the characteristics such as the background qualification, job position, working experience, and knowledge in the green industry. The data was transcribed by using paper and pen, and the thematic analysis was used. From the interview session, a total of eight elements has been identified in green skills namely; waste skills, design skills, planning, procurement, and material skills, energy and water skills, communication skills, management skills, leadership and teamwork skills, problem-solving and critical thinking skills. This exploration was useful in order to conduct the next round of Delphi technique in terms of checklist items among the experts.